2023
DOI: 10.3390/biomedicines11061621
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis for the Treatment of Fibromyalgia: A Systematic Review

Abstract: Fibromyalgia is a common disease syndrome characterized by chronic pain and fatigue in conjunction with cognitive dysfunction such as memory difficulties. Patients currently face a difficult prognosis with limited treatment options and a diminished quality of life. Given its widespread use and potential efficacy in treating other types of pain, cannabis may prove to be an effective treatment for fibromyalgia. This review aims to examine and discuss current clinical evidence regarding the use of cannabis for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…It was found a potential role for cannabinoids in reducing pain and improving measures of quality of life (QoL) in FM, but the results were largely varying across studies and further researches are needed to strength-en this low-quality evidence. However, the review reported no severe adverse events associated with this treatment (25). A recent prospective cohort study investigated the potential role of cannabis treatment (20 grams per month for 6 months, administered by smoking, vaporizing or ingestion) in a cohort of 30 women suffering from FM; it showed improvements in general QoL, physical and psychological domain after starting cannabinoid treatment (26).…”
Section: Pharmacological Therapymentioning
confidence: 99%
“…It was found a potential role for cannabinoids in reducing pain and improving measures of quality of life (QoL) in FM, but the results were largely varying across studies and further researches are needed to strength-en this low-quality evidence. However, the review reported no severe adverse events associated with this treatment (25). A recent prospective cohort study investigated the potential role of cannabis treatment (20 grams per month for 6 months, administered by smoking, vaporizing or ingestion) in a cohort of 30 women suffering from FM; it showed improvements in general QoL, physical and psychological domain after starting cannabinoid treatment (26).…”
Section: Pharmacological Therapymentioning
confidence: 99%
“…Cannabinoids are also being investigated for their potential analgesic and antiinflammatory properties [105]. Some studies suggest that cannabinoids may offer pain relief and improve sleep in individuals with fibromyalgia [106].…”
Section: Emerging Treatments and Researchmentioning
confidence: 99%